2018
DOI: 10.1038/s41419-017-0029-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Trop2 blockade enhances the therapeutic efficacy of ErbB3 inhibition in head and neck squamous cell carcinoma

Abstract: ErbB3 has been widely implicated in treatment resistance, but its role as a primary treatment target is less clear. Canonically ErbB3 requires EGFR or ErbB2 for activation, whereas these two established treatment targets are thought to signal independently of ErbB3. In this study, we show that ErbB3 is essential for tumor growth of treatment-naive HNSCC patient-derived xenografts. This ErbB3 dependency occurs via ErbB3-mediated control of EGFR activation and HIF1α stabilization, which require ErbB3 and its lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 53 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…In fact, decreased TROP-2 expression has been associated with HNSCC having sarcomatoid (spindle cell) tumors [ 52 ]. These authors also reported that combining antibodies against ErbB-3 and TROP-2 results in synergistic therapeutic responses in human HNSCC xenografts [ 134 ].…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…In fact, decreased TROP-2 expression has been associated with HNSCC having sarcomatoid (spindle cell) tumors [ 52 ]. These authors also reported that combining antibodies against ErbB-3 and TROP-2 results in synergistic therapeutic responses in human HNSCC xenografts [ 134 ].…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…In HNSCC, full EGF-R activation is dependent on the ErbB3-neuregulin axis. (Redlich et al, 2018). Compared with other tumours, HNSCC have among the highest levels of NRG1, and tumours recurrence further increases neuregulin-1 expression after curative treatments with radiation and chemotherapy .…”
Section: Growth Factor-mediated Signallingmentioning
confidence: 99%
“…Therefore, exploration of the specific gene responsible for osteoporosis and identification of new therapeutic targets are especially important. Previously, we found that GAS5 could negatively regulate the adipocyte differentiation ( Li et al, 2018 ). Herein, in our research, we found that as a protective target, GAS5 decreases in both bone tissue and BMSCs, a major origin of osteoblast, of patients with osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…GAS5 is a well-researched lncRNA that widely contributes to various cell biology functions such as immunity, tumor generation and metastasis ( Renganathan et al, 2014 ; Sun et al, 2017 ; Wang et al, 2016 ). In our previous study, we demonstrated that GAS5 negatively affected the adipoytes differentiation through the miR-18a /CTGF pathway ( Li et al, 2018 ). Other researchers also recognized the crucial role of GAS5 in BMSCs differentiation.…”
Section: Introductionmentioning
confidence: 99%